Oral manifestations of autoimmune connective tissue diseases - Akshat Pandey; Mimansha Pandey; Ved Prakash Pandey; Vinod Ravindran (Indian Journal of Rheumatology)
Autoimmune connective tissue diseases possess difficulty in diagnosis and treatment due to uncertainty in etiology, a wide array of clinical presentation, and unpredictable disease course. Many such diseases like Sjögren syndrome, Rheumatoid arthritis, Systemic Lupus Erythematosus, Systemic Sclerosis, have characteristic oral findings, the identification of which may allow for early diagnosis and treatment. For the purpose of this narrative review we searched the databases such as MEDLINE the Embase and Cochrane library using search terms including “rheumatic” “autoimmune,” “connective tissue diseases,” “dental,” “oral,” and “manifestations” and the names of individual known diseases and also a manual search of bibliographies of these articles and of previously published reviews and animal studies. In this review, we describe the oral manifestation and dental considerations associated with these diseases which will allow the practitioner in holistic management of these patients.